Decreased Klotho Expression Causes Accelerated Decline of Male Fecundity through Oxidative Injury in Murine Testis - Ya-Yun Wang; Ying-Hung Lin; Vin-Cent Wu; Yu-Hua Lin; Chia-Yen Huang; Wei-Chi Ku; Chiao-Yin Sun (MDPI AG, 2023)
Oxidative stress is the etiology for 30-80% of male patients affected by infertility, which is a major health problem worldwide. Klotho protein is an aging suppressor that functions as a humoral factor modulating various cellular processes including antioxidation and anti-inflammation, and its dysregulation leads to human pathologies. Male mice lacking Klotho are sterile, and decreased Klotho levels in the serum are observed in men suffering from infertility with lower sperm counts. However, the mechanism by which Klotho maintains healthy male fertility remains unclear. Klotho haplodeficiency (Kl+/−) accelerates fertility reduction by impairing sperm quality and spermatogenesis in Kl+/− mice. Testicular proteomic analysis revealed that loss of Klotho predominantly disturbed oxidation and the glutathione-related pathway. We further focused on the glutathione-S-transferase (GST) family which counteracts oxidative stress in most cell types and closely relates with fertility. Several GST proteins, including GSTP1, GSTO2, and GSTK1, were significantly downregulated, which subsequently resulted in increased levels of the lipid peroxidation product 4-hydroxynonenal and apoptosis in murine testis with low or no expression of Klotho. Taken together, the loss of one Kl allele accelerates male fecundity loss because diminished antioxidant capability induces oxidative injury in mice. This is the first study that highlights a connection between Klotho and GST proteins.